1996
DOI: 10.1007/bf00131288
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic buckling problem caused by propagation of stress wave in elastic cylindrical shells under impact torque

Abstract: The buckling problem of cylindrical shells has been studied by many mechanic researchers from different points of view. In this paper, an elastic cylindrical hli with semi-infinite length is studied. Let its dynamic buckling under impact torque be reduced to a b$.trcation problem caused by propagation of the torsional stress wave. The btfurcation problem is converted to a solution of nonlinear equations, the lateral inertia effect on the dynamic buckling is also discussed. Finally, numerical computation is car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…The results of this problem have some similarity with the results of Ref. [6], which the impact loads was taken as the step loading and the dynamic buckling was referred as the bifurcation caused by propagation of stress wave without reflection.…”
Section: Key Engineering Materials Vols 274-276supporting
confidence: 71%
See 1 more Smart Citation
“…The results of this problem have some similarity with the results of Ref. [6], which the impact loads was taken as the step loading and the dynamic buckling was referred as the bifurcation caused by propagation of stress wave without reflection.…”
Section: Key Engineering Materials Vols 274-276supporting
confidence: 71%
“…In Ref. [4,5,6] the dynamic buckling caused by the stress wave in cylindrical shells was studied, and the effects of the propagation of stress wave have been taken into account. For the dynamic buckling of cylindrical shells, which is subjected to an axial impact by a rigid body, less research has been so far made and no theoretical solution has been obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results of Tang Liqun [4] revealed that stress wave effect may have some influence on the dynamic buckling. Teng Ningjun [5] and Han Qiang [6] let the dynamic buckling of bars under step load be reduced to a bifurcation problem caused by the propagation of axial stress wave. Karagiozova D and Vaughn D G studied the influence of initial velocity on the dynamic buckling in different ways considering the stress wave effect [7][8][9][10] .…”
mentioning
confidence: 99%